Inactivation of escherichia coli and listeria monocytogenes with Nd: YAG laser and its harmonics - Kundwal, Moses Elisha (2016)
Ultraviolet (UV) lasers have been employed for many applications such as in the food industry, medicine and dentistry. The use of laser and other pulsed light systems for phototherapy and other microbial disinfections are based on spectral characteristics and configuration of the light used. The objective of this study was to use a flash lamp-pumped passive Q-switched Nd:YAG laser for inactivation two pathogenic bacteria, namely Escherichia coli and Listeria monocytogenes. A 1064 nm pulsed infrared (IR) laser and its 2nd and 3rd harmonics were used to irradiate Escherichia coli at various values of fluence. A 350 nm continuous wave (CW) UV lamp was also used in the inactivation process for the purpose of comparison with the 3rd harmonic (355 nm) pulsed laser. The result indicates that there is a statistical significant difference between mean log10 reductions for the three laser wavelengths. The mean log10 reductions for the 355 nm pulsed (UV) laser are higher than the corresponding mean log10 reductions for the CW UV light. A t-test conducted on the mean log10 reductions obtained for the pulsed UV laser and the CW UV light indicates that there is a significant difference between the two sets of mean log10 reductions. When E. coli and L. monocytogenes samples were irradiated with the pulsed UV laser at three different pulse frequencies, the result shows higher inactivation effect at higher pulse frequency than at lower pulse frequency. Statistical analysis, using two-way ANOVA, shows that the mean log10 reductions for the three pulsed frequencies were significantly different. However, no statistical significant difference was observed between mean log10 reductions obtained for treatment with the pulsed UV laser and the CW UV light on three different sample volumes of E. coli and L. monocytogenes.